The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/modpathol.2013.122
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing-based multi-gene mutation profiling of solid tumors using fine needle aspiration samples: promises and challenges for routine clinical diagnostics

Abstract: Increasing use of fine needle aspiration for oncological diagnosis, while minimally invasive, poses a challenge for molecular testing by traditional sequencing platforms due to high sample requirements. The advent of affordable benchtop next-generation sequencing platforms such as the semiconductor-based Ion Personal Genome Machine (PGM) Sequencer has facilitated multi-gene mutational profiling using only nanograms of DNA. We describe successful next-generation sequencing-based testing of fine needle aspiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
191
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(200 citation statements)
references
References 45 publications
4
191
1
Order By: Relevance
“…As a matter of the fact, most NGS assays have a lower limit of mutation detection of 10%, which requires at least 20% of neoplastic cells. 39 Besides NGS technological improvements, automated allele-specific real-time PCR technology is also advancing at a rapid pace. In particular, the fully automated molecular diagnostic system Idylla (Biocartis, Mechelen, Belgium) is a fascinating technology.…”
Section: Nucleic Acid Sample Quantity and Quality Assessmentmentioning
confidence: 99%
“…As a matter of the fact, most NGS assays have a lower limit of mutation detection of 10%, which requires at least 20% of neoplastic cells. 39 Besides NGS technological improvements, automated allele-specific real-time PCR technology is also advancing at a rapid pace. In particular, the fully automated molecular diagnostic system Idylla (Biocartis, Mechelen, Belgium) is a fascinating technology.…”
Section: Nucleic Acid Sample Quantity and Quality Assessmentmentioning
confidence: 99%
“…Therefore, different NGS platforms use FNC to harvest cells from different tumors [92,93,94,95,96,97,98,99,100]. These studies demonstrated that NGS-based mutational profiling can be performed with a few nanograms of DNA (∼40 ng/μl), which can be easily obtained from FNC in different tumors [93,94,95,96,97,98]. Therefore, NGS may enhance the molecular FNC potential, providing mutational information on genes with high diagnostic and predictive relevance, such as EGFR, BRAF, K/N/HRAS, KIT, PTEN, CDKN2A, just to mention some, thus contributing to personalized therapies.…”
Section: High-throughput Technologies-based Arraysmentioning
confidence: 99%
“…The Viewpoint The use of endobronchial ultrasound guided transbronchial needle aspiration specimens for next generation sequencing in non-small cell lung cancer: a clinical perspective adequacy of a cell block cannot be reliably assessed intraprocedurally. The importance of adequate sample cellularity is highlighted by prior studies which describe the successful technique of extracting DNA from cytology slides prepared with fine needle aspiration (FNA) tumor samples (17)(18)(19)(20)(21). These studies demonstrate a direct relationship between successful NGS testing and increased slide cellularity.…”
Section: Introductionmentioning
confidence: 91%